Intensive Parenting Training Based on Child Protection Through the Rapid Rural Appraisal (RRA) Method of Field Study in Blitar Regency - Muhammad Sholihuddin Zuhdi (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
In the current era, many parents are too busy to work with the aim of meeting their daily needs and social demands, in the end there are some parents who ignore their children or often scold their children because they are tired of their work. Improper treatment of children will have a negative impact on children. In this paper, we will discuss parenting training for parents who have difficulty in raising children. The method used is the Rapid Rural Appraisal (RRA) Method or Rapid Rural Assessment, this is a method of assessing the situation and conditions in an area (village), the quick step here is to find data and information quickly from various sources. In this service, data and information were obtained from the community, the child protection commission of the Wonodadi sub-district, as well as influential figures in the Pikatan village community. The result of the training is that there is a change in parents who initially have an authoritarian parenting pattern that gradually improves and applies parenting in accordance with the needs of the child.